Approximation of general zero-range potentials - Albeverio, S.; Nizhnik, L. P. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
A norm resolvent convergence result is proved for approximations of general Schrodinger operators with zero-range potentials. An approximation of the δ’-interaction by nonlocal non-Hermitian potentials (without a renormalization of the coupling constant) is also constructed.